Measuring Consumption Externalities - Emanuela Randon (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Estimation and measurement of consumption externalities are still challenging problems in applied research. In this paper, externalities as Nash equilibrium are estimated using consumer demand theory and a large data set. We estimate Nash equilibrium consumption externalities in petrol budget shares of households living in a metropolitan area in UK. The reaction curves are derived from an Almost Ideal Demand System (AIDS) with externalities. A continuous set of ten year cross sections from the Family Expenditure Surveys is used. In each year, income decile cohorts are created. Results of 2SLS with Panel Data are presented after 2SLS estimates with pooling cross sections have been discussed. Results give evidence that the household petrol consumption pattern is explained by income and externality variables. We also suggest that in order to internalise the negative externality effect, households should be taxed independently of household income.
Keywords: C31; C33; C72; D12; D62; 330